2002
DOI: 10.1258/135763302320272176
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of videoconferenced grand rounds

Abstract: We evaluated various aspects of grand rounds videoconferenced from a tertiary care hospital to a regional hospital in Nova Scotia. During a five-month study period, 29 rounds were broadcast (19 in medicine and 10 in cardiology). The total recorded attendance at the remote site was 103, comprising 70 specialists, nine family physicians and 24 other health-care professionals. We received 55 evaluations, a response rate of 53%. On a five-point Likert scale (on which higher scores indicated better quality), mean r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
0
20
1
1
Order By: Relevance
“…9 Videoconference-based education for psychiatry registrars at the University of KwaZulu-Natal, South Africa Videoconference-based education is an integral component in many telehealth services in countries such as Australia 10 and include activities such as journal clubs, ward rounds, continuing and formal medical education. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Studies evaluating these activities have reported general satisfaction with the use of videoconferencing and no difference in educational outcomes compared to traditional face to face teaching. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The Nelson R Mandela School of Medicine at the University of KwaZulu-Natal has increased the psychiatry registrar posts three-fold over the last three decades.…”
Section: Videoconference-based Teachingmentioning
confidence: 99%
“…9 Videoconference-based education for psychiatry registrars at the University of KwaZulu-Natal, South Africa Videoconference-based education is an integral component in many telehealth services in countries such as Australia 10 and include activities such as journal clubs, ward rounds, continuing and formal medical education. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Studies evaluating these activities have reported general satisfaction with the use of videoconferencing and no difference in educational outcomes compared to traditional face to face teaching. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] The Nelson R Mandela School of Medicine at the University of KwaZulu-Natal has increased the psychiatry registrar posts three-fold over the last three decades.…”
Section: Videoconference-based Teachingmentioning
confidence: 99%
“…For the field of radiation oncology, this product could provide main hospitals and their satellite institutions with a cost-effective platform to conduct both virtual tumor boards and dosimetry conferences with participating institutions. [22][23][24][25] Although this prototype solution was not adopted by our program, the lessons learned enabled us to develop the vastly superior system we have now (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…We, as well as others, have previously found similar results when polling remote attendees. [5][6][7][8] In this study, however, we attempted to compare evaluations from 650 CME conferences that had both inperson and remote conference attendees. Evaluation responses were generally lower for telemedicine attendees ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…While this could be expected for affected small group sessions, it can also be problematic for larger, Grand Rounds-style programs. 5,7 Thankfully, we have migrated away from projector slides over the course of this study and can now directly transmit electronic presentations, which has improved quality over our previous experience. 5 Still, in this study, the audio quality was rated excellent or good only 73% of the time, and video quality was considered excellent or good only 64% of the time.…”
Section: Discussionmentioning
confidence: 99%